Long non‐coding RNA UCA1 contributes to the progression of oral squamous cell carcinoma by regulating the WNT/β‐catenin signaling pathway. Issue 11 (4th November 2016) - Yang, Yong‐Tao; Wang, Yu‐Fan; Lai, Ju‐Yi; Shen, Shi‐Yue; Wang, Feng; Kong, Jie; Zhang, Wei; Yang, Hong‐Yu
Abstract : With the development of functional genomics studies, a mass of long non‐coding RNAs (LncRNA) were discovered from the human genome. Long non‐coding RNAs serve as pivotal regulators of genes that are able to generate LncRNA–binding protein complexes to modulate a great number of genes. Recently, the LncRNA urothelial carcinoma‐associated 1 (UCA1) has been revealed to be dysregulated, which plays a critical role in the development of a few cancers. However, the role of the biology and clinical significance of UCA1 in the tumorigenesis of oral squamous cell carcinoma (OSCC) remain unknown. We found that UCA1 expression levels were upregulated aberrantly in tongue squamous cell carcinoma tissues and associated with lymph node metastasis and TNM stage. We explored the expression, function, and molecular mechanism of LncRNA UCA1 in OSCC. In the present work, we revealed that UCA1 silencing suppressed proliferation and metastasis and induced apoptosis of OSCC cell lines in vitro and in vivo, which might be related to the activation level of the WNT/β‐catenin signaling pathway. Our research results emphasize the pivotal role of UCA1 in the oncogenesis of OSCC and reveal a novel LncRNA UCA1–β‐catenin–WNT signaling pathway regulatory network that could contribute to our understanding in the pathogenesis of OSCC and assist in the discovery of a viable LncRNA‐directed diagnostic and therapeutic strategy for this fatal disease. Abstract : Our data highlighted the pivotal role of UCA1 in the tumorigenesis of oral squamous cell carcinoma, and revealed a novel LncRNA UCA1‐β‐catenin‐Wnt signaling pathway regulatory network, which may contribute to understand the pathogenesis of oral squamous cell carcinoma.